2015
DOI: 10.4187/respcare.03953
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Outcomes of Subjects With Severe Community-Acquired Pneumonia Using Monocyte Human Leukocyte Antigen-DR

Abstract: BACKGROUND:The objective was to study the level of monocyte-human leukocyte antigen-DR (mHLA-DR), an immune function-related biomarker, at 24 h after admission, to predict the outcomes of subjects with severe pneumonia. METHODS: Subjects with severe community-acquired pneumonia (n ‫؍‬ 102) were included in the study. Blood samples were collected from each subject 24 h after admission. Data regarding age, sex, P aO 2 /F IO 2 , comorbidities, occurrence of altered mental status, bacteremia, septic shock, Acute P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Depressed expression of HLA-DRA in monocytes and dendritic cells has been found in patients with sepsis, probably due to an increased apoptosis of lymphoid cells or T-cell exhaustion. Zhuang et al [9] reported that patients with mHLA-DR ≥27.2% had significantly better outcomes compared to those with levels of <27.2%. Inducible T cell co-stimulator (ICOS) is involved in directing effector T cell differentiation and has an important role in adaptive immunity [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depressed expression of HLA-DRA in monocytes and dendritic cells has been found in patients with sepsis, probably due to an increased apoptosis of lymphoid cells or T-cell exhaustion. Zhuang et al [9] reported that patients with mHLA-DR ≥27.2% had significantly better outcomes compared to those with levels of <27.2%. Inducible T cell co-stimulator (ICOS) is involved in directing effector T cell differentiation and has an important role in adaptive immunity [21].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, sepsis [5] and ventilator-associated pneumonia (VAP) are characterized by the depression of the immunological synapse [6]. However, there is scarce information of immunological signatures at the transcriptomic level in CAP in non-critically ill patients, despite the fact that CAP is one of the most frequent infections causing sepsis [7,8] and that it has a potential association with endothelial damage [9].…”
Section: Introductionmentioning
confidence: 99%
“…In sepsis, the mHLA-DR decreases rapidly in correlation to the severity and outcome of the septic shock [94,95]. Zhuang et al [96] studied the expression of mHLA-DR by cytometry 24 h after admission to predict the 28-day survival of CAP patients. They reported that nonsurvivors significantly expressed reduced levels of mHLA-DR on their monocyte membranes [96].…”
Section: Monocyte Human Leukocyte Antigen-dr (Mhla-dr)mentioning
confidence: 99%
“…Zhuang et al [96] studied the expression of mHLA-DR by cytometry 24 h after admission to predict the 28-day survival of CAP patients. They reported that nonsurvivors significantly expressed reduced levels of mHLA-DR on their monocyte membranes [96]. There is still not enough evidence whether mHLA-DR could be a useful marker in CAP.…”
Section: Monocyte Human Leukocyte Antigen-dr (Mhla-dr)mentioning
confidence: 99%
“…In this regard, Davenport et al, using a transcriptomic analysis, found a gene expression signature (SRS1) which identifies individuals with an immunosuppressed phenotype and higher 14-day mortality within a cohort of patients with sepsis secondary to CAP ( Davenport et al, 2016 ). In addition, new biomarkers such as expression of HLA-DR on monocytes ( Zhuang et al, 2015 ), soluble CD14 (presepsin) ( Klouche et al, 2016 ), interleukins ( Menéndez et al, 2009 ; Andrijevic et al, 2014 ), procalcitonin ( Liu et al, 2016a ), and mid-regional pro-ADM ( Liu et al, 2016b ) could help risk assessment in the early stages of the disease. As an alternative to these new sophisticated (and expensive)“omics” and biomarker-based approaches, a simple leukogram has shown potential to be a tool for classifying patients with CAP or sepsis based on their outcomes.…”
Section: Introductionmentioning
confidence: 99%